2022
DOI: 10.1007/s00134-021-06615-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health symptoms in family members of COVID-19 ICU survivors 3 and 12 months after ICU admission: a multicentre prospective cohort study

Abstract: Purpose Long-term mental outcomes in family members of coronavirus disease 2019 (COVID-19) intensive care unit (ICU) survivors are unknown. Therefore, we assessed the prevalence of mental health symptoms, including associated risk factors, and quality of life (QoL) in family members of COVID-19 ICU survivors 3 and 12 months post-ICU. Methods A prospective multicentre cohort study in ICUs of ten Dutch hospitals, including adult family members of COVID-19 ICU survivors ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
28
1
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
10
28
1
7
Order By: Relevance
“…We observed only a slight decrease in the role emotional dimension in the participants, possibly as a result of the general measures in managing the COVID-19 pandemic [ 21 ]. This finding is in line with the results of several other studies reporting a decline in QoL among COVID-19-survivors, depending on sociodemographic factors and belief in the negative effects of recent SARS-CoV-2-infection [ 22 ], which has also been observed in family members of ICU COVID-19-survivors [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…We observed only a slight decrease in the role emotional dimension in the participants, possibly as a result of the general measures in managing the COVID-19 pandemic [ 21 ]. This finding is in line with the results of several other studies reporting a decline in QoL among COVID-19-survivors, depending on sociodemographic factors and belief in the negative effects of recent SARS-CoV-2-infection [ 22 ], which has also been observed in family members of ICU COVID-19-survivors [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another study showed that the family members of COVID-19 patients experienced mental health symptoms 12 months after ICU admission of their relatives for COVID-19 infection. Family members also experienced disruption of quality of life and work-related problems [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower education level and family history of psychiatric disorder were risk factors for anxiety, and home isolation was a risk factor for depression [ 15 ]. Aside from patients, there were few studies that showed that family members taking care of COVID-19 patients also experienced mental health impacts, including anxiety and depressive symptoms [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing knowledge about COVID-19, little is still known about the one-year consequences for ICU-survivors, and even less for their family members. A recently published study described the clinical outcomes of patients one year after COVID-19-related ICU-admission ( Heesakkers et al, 2022a ). Another study described the psychological consequences faced by the family members of COVID-19 ICU-survivors ( Heesakkers et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%